Simple Method for Determining Urinary Salt and Potassium Excretions for Seven Days - Takemori, Koichi; Asada, Yutaka; Yamamoto, Harue; Mikami, Seiji (Japanese Journal of Cardiovascular Disease Prevention, 2003)
Urinary salt (NaCl) and potassium (K) excretion in an individual is subject to day to day fluctuations. As a result, the method for determination of usual mean values requires daily measurement over a 7 or 14 day period. A simple method for measuring mean excretion over a 7 day period using filter paper absorption was tested on 115 subjects who participated in a sodium restriction health education program. Urine specimens were gathered as follows : 1.The second morning voiding urine was adsorbed onto a piece of filter paper and dried. 2.Samples were collected for each of consecutive seven days. 3.The seven filter papers were stacked and a longitudinal cut was made of about 1 mm width from the edge of the papers. 4.From this combined sample and each seven pieces of the rest, the urinary components, sodium (Na), K and creatinine (Creat) were extracted and concentrations measured. Using the predictive equations by Kawasaki et al., 24 hours urinary NaCl and K excretion were calculated. The correlation between the combined 7 samples and the mean of the 7 days were calculated. The respective correlation coefficients and the regression equations for NaCl, K, and Na-K ratio were : r=0.942 (p<0.001), y=1.0448x+0.5213; r=0.932 (p< 0.001), y=1.0455x+0.0262; r=0.903 (p<0.001), y=1.1128x-0.0013. The results show that there were no significant differences for NaCl, K, and Na-K ratio between the mean values over 7 days and the average presumptive value calculated by substituting the combined measured values in the regression equations. This method may provide a simplified way for quantifying excretion of these urinary components during the period of time studied.